Detection and discrimination of SARS-CoV-2 spike protein-derived peptides using THz metamaterials - 이수현; 이연경; 이상훈; 곽지성; 송현석; 서민아 (Pergamon Press Ltd., 2022)
The development of effective assay techniques for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has recently received research attention due to its rapid worldwide spread and considerable risk to human health. The receptor-binding domain (RBD) of the spike (S) protein in SARS-CoV-2, a key component for viral entry that has a unique sequence compared to other structural proteins, has been considered an important diagnostic target. In this respect, low-frequency vibrational modes have the advantage of providing information about compositional and structural dependencies at the peptide level. In this study, the sensitive and selective detection of peptides derived from the RBD in SARS-CoV-2 and SARS-CoV was investigated using metamaterial-based sensing chips with a terahertz time-domain spectroscopy (THz-TDS) system. Based on their RBD sequences, two pairs of peptides with 20 residues each were prepared. The sensitivity, specificity, and reproducibility of the proposed system were examined via quantitative analysis using THz metamaterials at three resonance frequencies, and it was found that the species could be discriminated based on their sequences. The THz signals were analyzed with regard to the major amino acid components of the peptides, and the molecular distributions were also investigated based on the hydropathy and net charge of the peptides. ？ 2022 The Authors